Criminal Protection Asylum in the Law of the Republic of Serbia - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
It is a rule in all modern criminal legislation, and so in the legislation of the Republic of Serbia, that after the criminal procedure, the competent court pronounces the type and the measure of punishment or other criminal sanction, to each criminal responsible for the criminal offence. This rule applies to both a Serbian citizen and an alien who is a perpetrator of a criminal offence. Under the law, the asylum institutes are also assisted by the conditions provided for in the exercise of the criminal law's protective function. Asylum protects the human rights of foreigners (or stateless persons) from criminal prosecution for certain offences based on discrimination of any kind. This institute is closely linked to migrants and migration. Asylum is granted to foreigners by the competent state authorities of the home state under certain conditions and in a certain procedure. However, various forms of abuse of asylum are possible, for which domestic law prescribes criminal responsibility and punishment. It is precisely about asylum and the criminal protection against various forms of abuse under the law of the Republic of Serbia, in light of the protection of migrants' human rights.